2019
DOI: 10.11646/zootaxa.4661.3.1
|View full text |Cite
|
Sign up to set email alerts
|

A new and most complete pampathere (Mammalia, Xenarthra, Cingulata) from the Quaternary of Bahia, Brazil

Abstract: Pampatheriidae is a group of South American native cingulates recorded from the Middle Miocene to the Early Holocene. These animals arrived in North America during the Great American Biotic Interchange. During the Quaternary, at least three genera existed: Tonnicinctus Góis, González Ruiz, Scillato-Yané and Soibelzon, Pampatherium Gervais and Ameghino, and Holmesina Simpson. They are differentiated mainly by craniodental and osteodermal characters. In this paper, we describe a new species of Holmesina from Bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This contrasts with other cingulate lineages, which survived until the Late Pleistocene or Early Holocene (glyptodonts, pampatheres; Moura et al . 2019; Politis et al . 2019) or have extant representatives (chlamyphorids, dasypodids; Abba & Vizcaíno 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with other cingulate lineages, which survived until the Late Pleistocene or Early Holocene (glyptodonts, pampatheres; Moura et al . 2019; Politis et al . 2019) or have extant representatives (chlamyphorids, dasypodids; Abba & Vizcaíno 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although this feature does not have an impact on the large pattern, it has an obvious impact on the crowd. Within crowds C, D, and E, the differences of BGU between continents become smaller, and the independence of islands increases, such as BGU 35,36,37,38,49,58 and 69.…”
Section: Discussionmentioning
confidence: 99%
“…The data source of this study is the monograph of zoologists [30,31]; Floristic data collated by professional biodiversity websites [32]. In addition, new species and new distribution records published by taxonomists will be supplemented at any time [33][34][35][36]. In the mammal fauna data of 20,867 species in 29 orders, excluding deep-sea species and fossil species, there are 7,591 species of terrestrial mammals in 27 orders, 162 families, 1,374 genera for analysis (Table 1).…”
Section: Global Terrestrial Mammal Faunamentioning
confidence: 99%
“…The species Holmesina paulacoutoi, Holmesina major , Holmesina rondoniensis (Góis et al, 2012), and Holmesina cryptae (Moura et al, 2019) are reported for Brazil. The osteoderms described here (Figure 2P) have features consistent with H. paulacoutoi, including more pronounced ornamentation than in H. cryptae, a welldeveloped longitudinal central elevation (poorly developed in H. major and comparatively low in H. cryptae), and shallow lateral depressions (deep in H. major) (see Góis, 2013;Moura et al, 2019). There are no osteoderms described for H. rondoniensis for comparison.…”
Section: Holmesina Simpson 1930mentioning
confidence: 97%